Structural characterisation and Kerr magnetometry of Fe/Mo(110) epitaxial system - Usov, Victor (Trinity College (Dublin, Ireland). School of Physics, 2005)
This thesis describes the investigation of the growth and magnetic properties of ultrathin Fe films on the Mo(110) surface. The surface magneto optical Kerr effect (SMOKE) setup was designed and built by author and used in conjunction with the surface characterisation techniques to study magnetic anisotropy and magnetic phase transition in Fe/Mo(110) films. The emphasis is made on correlation between magnetic properties and film morphology.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin